The Code-mixing Used by Nadiem Anwar Makarim on Chosen Youtube Video - Heru Priyatna; Dwi Rukmini; Hendi Pratama (Universitas Negeri Semarang, 2022)
Mixing two or more languages in the same conversation is a common phenomenon in this modern era. Furthermore, many people, particularly entertainers and also people in government such as Nadiem Anwar Makarim, the Ministry of Education and Culture, also used code-mixing. The present study is aimed at investigating the code-mixing used by Nadiem Anwar Makarim. This qualitative research is conducted by observing and analyzing the utterances from downloaded video podcasts as the data, which was then transcribed. The data analysis also included the types and factors of code-mixing. There were 173 numbers of data from the types of code-mixing, and those data were divided into three types. Those are 90 numbers of intra-sentential data, 81 numbers of intra-lexical data, and 2 numbers of pronunciation changes. The finding shows that intra-sentential code-mixing is the most frequent type used by Nadiem Makarim. Furthermore, the researchers also found the factors of code-mixing, which are internal factors and external factors. This study is significant for several reasons. First, the findings of this research are expected to be a meaningful description of the existence of code-mixing. It can be used to support daily conversation, especially in the teaching and learning processes. This study is also expected to be meaningful information for further research in the future for a better understanding of the use of code-mixing.